REFORM IN UPPER SECONDARY SCHOOL GOVERNANCE TOWARDS AUTONOMY MODEL: A CASE STUDY OF REALITY AUTONOMY MODEL IN VIETNAM - Huong, Nguyen Thi; Pham, Phuong Thu (International Journal of Psychosocial Rehabilitation, 2020)
In Vietnam, general education includes primary education, lower secondary education (the period of basic education) and upper secondary education (the period of vocational orientation education). In particular, primary education is compulsory for all children from 6 to 14 years old, is implemented in 5 school years, from first grade to fifth grade. The age of students entering first grade is six years old. Primary education aims to help students form the initial foundations for proper and long-term development of morality, intelligence, physicality, aesthetics and basic skills for students to continue high school. Secondary education is conducted in four school years, from grade six to grade nine. Students entering sixth grade must have an elementary school diploma. Secondary education aims to help students consolidate and develop the results of primary education; have basic secondary education and initial knowledge about technology and career to continue high school, vocational high school, vocational training or enter a working life. High school education is conducted in 3 school years, from grade ten to grade twelve. Students entering tenth grade must have a junior high school diploma. High school education is aimed at helping students consolidate and develop the outcomes of lower secondary education, complete high school education and common knowledge about technology and career guidance for further college education, college, professional secondary school, apprenticeship or enter the working life. Thus, the term general education is a term with broad connotation including primary education, lower secondary education (basic education period) and upper secondary education (education period) career orientation. Within the scope of this research, we use the term school governance used to mean a mode of action, which is directed toward the goal of being accomplished effectively, by and through others. Governance activities are indispensable activities that arise when people work together to accomplish goals.